TEACHING VOCABULARY THROUGH â€œRIDDLESâ€ - Wiwin, Angelia Meliani; Sutapa Y, Y. Gatot; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to provide information about the effectiveness of teaching vocabulary through riddle. The method of this research is a pre-experimental research. The data were taken from the objective test that was given to students. The test consists of 25 items of pre-test and 25 items of post-test, in the form of short-answer questions (riddle). This research was done to 31 students as the sample. From the result of the analysis, the researcher found that there is the improvement of the studentsâ€™ mean score. The studentsâ€™ mean score of post-test is higher than the studentsâ€™ mean score of pre-test. The result of t-test was higher than t-table. The effect size of the using riddle in teaching vocabulary on the eighth grade students of SMP N 1 BengkayangÂ in academic year 2013/2014 is 1.97 (One point ninety seven) which qualified high. Based on that, it can be concluded that the use of riddle in teaching vocabulary can increase studentsâ€™ English vocabulary. Â Key word: Riddle, Vocabulary. Â Abstract: Tujuan dari penelitian ini adalah untuk menyampaikan informasi mengenai keefektifan dalam pengajaran kosa kata melalui penggunaan Riddle (teka-teki). Metode yang digunakan dalam penelitian ini adalah pre-Experimental research. Data diambil melalui tes objektif yang diberikan kepada siswa. Tes yang terdiri darri 25 item pre â€“test dan 25 item post-test,Â dalam bentuk pertanyaan singkat (Riddle/teka-teki). Dari hasil analisis, peniliti menemukan peningkatan pada nilai rata-rata siswa. Nilai rata-rata post-test siswa lebih tinggi dari nilai rata-rata pre-test nya. Nilai t-test lebih tinggi dari Nilai t-table. Nilai effect size dari penggunaan riddle dalam pengajaran kosa kata adalah 1. 97 yang dikualifiaksikan pada level tinggi. Berdasarkan hal itu, dapat disimpulakn bahwa penggunaan riddle dalam pengajaran kosakata dapat meningkatkan pemahaman kosa kata bahasa inggris siswa. Â Kata Kunci: Riddle (teka-teki), kosakata.